Cellular microstructures superposed on martensite plates in Mn55.2Ga19.0Cu25.8 alloy showing large coercivity. (1st July 2017) - Sawada, R.; Yamamoto, T.; Minakuchi, K.; Nagasako, M.; Hayasaka, Y.; Niitsu, K.; Cho, Y.; Kainuma, R.; Murakami, Y.
Abstract: The microstructure in a Mn55.2 Ga19.0 Cu25.8 alloy that exhibits both martensitic and diffusional phase transformations was examined by electron microscopy, and the potential effects of these transformations on the large coercivity ( 2 T) were discussed. The alloy showed a cellular microstructure, composed of a cuboidal matrix enveloped by a boundary phase, and superposed on well-defined martensite plates. Since the boundary phase is enriched by the non-magnetic element Cu, it may serve as magnetic isolation for the matrix region with a face centered tetragonal lattice formed by the martensitic transformation, or offer potential pinning sites for magnetic domain walls. Graphical abstract: